Urban transport interchanges: A methodology for evaluating perceived quality. (February 2016) - Hernandez, Sara; Monzon, Andres; de Oña, Rocío
Highlights: Influence of urban transport interchanges on travellers' daily experience. Analysis of the users' perception of different aspects of an interchange. Deduction of the importance of each attribute through regression tree model. Identification of action priorities through importance-performance analysis. Information provision and safety and security conditions are key aspects for users. Abstract: Travel patterns in urban areas are becoming increasingly complex, and many public transport users need to transfer between different modes to complete their daily trips. Transport interchanges play a key role as urban transport network nodes, and the quality of the service provided in an urban transport interchange therefore has a direct influence on travellers' daily experience. This study proposes a useful methodological framework to identify the potential strengths and weaknesses of urban transport interchanges and to manage resources more efficiently. It is based on a two-step analytical procedure combining the classification and regression tree model and importance-performance analysis. A travellers' attitudinal survey was carried out in the Moncloa transport interchange (Madrid, Spain) and the methodological framework was applied to the data collected. The greatest strengths of the interchange from the users' point of view are the information provision through signposting, the features of the internal design of the interchange which have a direct influence on aspects related to safety performance, and security conditions, particularly during day-time.